Palm oil in milk: how the European Union strengthens its presence on the West African dairy market by selling a milk powder substitute - (:unkn) unknown (My University, 2020)
This paper discusses the recent boom in trade of blends of skimmed milk powder & palm oil between the EuropeanUnion and West Africa. Due to tensions on international markets of milk ingredients, and in response to strong localdemand for dairy raw materials, imports of these "fat-filled blends" in West Africa have exceeded purchases of milkpowders. Imports of blends from the EU, in particular, have quadrupled since the 2000s, reaching 324,000 tonnesin 2019. Blends of skimmed milk powder & vegetable fats now account for 40% of the total value of imports of dairyproducts in the region. In this context, proper labelling and information to consumers are of particular importance toavoid unfair practices. Several associations and producers’ organizations also question the underlying food andeconomic models with potential impacts on human health, environment and rural development. Due to the weakprotection of local markets, these substitutes hamper the development of local dairy farming.
Keywords: African Research